Interfacial tension approach toward drug loading with two-dimensional crosslinked polymer embedded gold: adsorption kinetics evaluation - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (International Journal Of Polymeric Materials And Polymeric Biomaterials, 2016)
Interfacial tension of drugs with hydrophilic polymer (A) embedded gold resulting into selective drug adsorption, which also affected the drug adsorption kinetics. Two-dimensional crosslinked polymer embedded gold was synthesized for drug loading application in an acidic buffer. Lower interfacial tension of pantoprazole sodium (B) revealed the exponential loading inversely loading was gradual for chloroquine (C) having more interfacial tension with adsorbent. Initial 2 h was the exponential adsorption period for a pantoprazole sodium whereas exponential adsorption begins after 12 h for a chloroquine. Monolayer drug adsorption was obtained because Langmuir adsorption isotherm was obeyed by both drugs. Moreover, pseudo first-and pseudo second-order kinetics was also evaluated which demonstrated that reactive sites of the adsorbent are homogeneous and drug adsorption mechanism is chemisorption and not the physisorption. Thermal analysis was evaluated to confirm the polymer thermostability and glass transition temperature during catalytic applications in thermal reactions.
Keywords: Adsorption isotherm; adsorption kinetics; drug loading; drug polarity; Interfacial tension